-3(-3x+3)=5-2x-3x

Simple and best practice solution for -3(-3x+3)=5-2x-3x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -3(-3x+3)=5-2x-3x equation:


Simplifying
-3(-3x + 3) = 5 + -2x + -3x

Reorder the terms:
-3(3 + -3x) = 5 + -2x + -3x
(3 * -3 + -3x * -3) = 5 + -2x + -3x
(-9 + 9x) = 5 + -2x + -3x

Combine like terms: -2x + -3x = -5x
-9 + 9x = 5 + -5x

Solving
-9 + 9x = 5 + -5x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '5x' to each side of the equation.
-9 + 9x + 5x = 5 + -5x + 5x

Combine like terms: 9x + 5x = 14x
-9 + 14x = 5 + -5x + 5x

Combine like terms: -5x + 5x = 0
-9 + 14x = 5 + 0
-9 + 14x = 5

Add '9' to each side of the equation.
-9 + 9 + 14x = 5 + 9

Combine like terms: -9 + 9 = 0
0 + 14x = 5 + 9
14x = 5 + 9

Combine like terms: 5 + 9 = 14
14x = 14

Divide each side by '14'.
x = 1

Simplifying
x = 1

See similar equations:

| p+p+16+4p-26=1046 | | 4(x+2)-(2x-5)= | | (-4)-(-3n)=-14-6n | | 4m-16=28 | | -7*2= | | 5n+7=7(n+1)-3n | | R=5x+14 | | 7x+3y-x+4y-2x= | | -3x-8+14=17 | | 8-9n=0 | | 9+3x=63 | | 2z-8=-0.5(3-5z) | | x+8x-6x-5= | | 0.9x-0.7y=6.8 | | 10+8c+7c=-10+10c | | 436.00=170+.95x | | 0.4k^2+0.2k-2=0 | | b(10b+3)=7 | | 7b+3+5b=-3b+8 | | 5x^2(3x)= | | Z^2-1z=42 | | .75n+5=n+1/.5 | | 78x-91=8x-2 | | 2x-(6-x)+4x+6=7x+2 | | -2n(2n+3)=4 | | -x-x=x-4x | | 400x-0.85=600x+0.23 | | -3x+25=5x-24 | | 3(3n+9)=7n-3 | | 9m+21=15m-21 | | 2(3x-3)=4(-x+11) | | x^2=4(x+224) |

Equations solver categories